DIGITAL SKILLS COUNSELING FOR GENERATION Z: A MASS COMMUNICATION PERSPECTIVE AT MADRASAH ALIYAH MIFTAHUL FALAH BANDUNG CITY - Herlina, Elin; Kusumadewi, Ade Nurhayati; Priyana, Indarta; Kusnara, Hasti Pramesti; Jaya, Umban Adi (LPPM Universitas Bina Bangsa, 2024)
The development of digital media enhances creativity but also raises ethical issues. Users need digital communication skills to get positive effects. The purpose of this counseling is to determine the ability of digital communication skills of Generation Z at Madrasah Aliyah Miftahul Falah, Bandung City, as the next generation of the nation towards the Golden Indonesia 2045. This counseling uses a qualitative approach, using a case study approach to six Generation Z participants who come from schools at Madrasah Aliyah Miftahul Falah, Bandung City, The techniques used in the qualitative research method of the case study approach focus on observation and in-depth interviews with 6 informants consisting of three students and three female students, Using mass communication theory developed by McQuail, The results of the counseling show that Generation Z has a fairly good level of digital literacy, as evidenced by their ability to choose websites that can be trusted and communicate digitally well on social media. The findings obtained, generation Z students, understand the importance of upholding digital communication standards, as well as how to overcome ethical dilemmas that arise online, especially on social media. However, the emergence of social media also raises digital communication problems such as the spread of hoaxes, doxing, bullying, cyberbullying, fraud, and negative online behaviors that have an impact on the education sector